Does performance at medical school predict success at the Intercollegiate Membership of the Royal College of Surgeons (MRCS) examination? A retrospective cohort study - Jennifer Cleland; Peter A Brennan; Amanda J Lee; Ricky Ellis; Duncan S G Scrimgeour (BMJ Open)
Background Identifying predictors of success in postgraduate examinations can help guide the career choices of medical students and may aid early identification of trainees requiring extra support to progress in specialty training. We assessed whether performance on the educational performance measurement (EPM) and situational judgement test (SJT) used for selection into foundation training predicted success at the Membership of the Royal College of Surgeons (MRCS) examination.Methods This was a longitudinal, cohort study using data from the UK Medical Education Database (https://www.ukmed.ac.uk). UK medical graduates who had attempted Part A (n=2585) and Part B (n=755) of the MRCS between 2014 and 2017 were included. χ2 and independent t-tests were used to examine the relationship between medical school performance and sociodemographic factors with first-attempt success at MRCS Part A and B. Multivariate logistic regression was employed to identify independent predictors of MRCS performance.Results The odds of passing MRCS increased by 55% for Part A (OR 1.55 (95% CI 1.48 to 1.61)) and 23% for Part B (1.23 (1.14 to 1.32)) for every additional EPM decile point gained. For every point awarded for additional degrees in the EPM, candidates were 20% more likely to pass MRCS Part A (1.20 (1.13 to 1.29)) and 17% more likely to pass Part B (1.17 (1.04 to 1.33)). For every point awarded for publications in the EPM, candidates were 14% more likely to pass MRCS Part A (1.14 (1.01 to 1.28)). SJT score was not a statistically significant independent predictor of MRCS success.Conclusion This study has demonstrated the EPM’s independent predictive power and found that medical school performance deciles are the most significant measure of predicting later success in the MRCS. These findings can be used by medical schools, training boards and workforce planners to inform evidence-based and contemporary selection and assessment strategies.